Bahagia Karena Allah: Religiusitas Sebagai Mediator Antara Komunikasi Intim Dan Kepuasan Perkawinan Pada Wanita Yang Menikah Dengan Cara Ta’aruf - Setiawati Intan Savitri; Arifah Hidayati (Program Studi Psikologi Islam, Fakultas Psikologi, Universitas Islam Negeri Raden Fatah Palembang, 2019)
Marriage satisfaction is caused by many factors. From various researches it was concluded that there are two main factors that cause marital satisfaction, namely communication and socio-economics. Among social factors, there are factors that encourage marital satisfaction, namely religiosity. In these two decades the practice of marriage without dating, which is often referred to as ta'aruf, is an expression of religious behavior. Although there are several studies linking the variables of intimate communication, religiosity and marital satisfaction, there is no research that explains the relationship of intimate communication and marital satisfaction with religiosity as mediator variables in the context of ta'aruf. The purpose of this research is to find evidence whether religiosity mediates the relationship between intimate communication and marital satisfaction. The sample of this study consisted of 150 women living in Tangerang who all underwent ta'aruf before marriage, with a marriage age of 1 to 25 years of marriage. Samples were obtained from study groups who practice ta'aruf as expressions of religious teachings, using a purposive method. Mediation analysis was performed by regression analysis of the PROCESS V3.0 procedure with SPSS version 2.5. The importance of religiosity in explaining the relationship between intimate communication and the satisfaction of Muslim marriages is discussed and discussed.